Respuesta :
Answer:
Step-by-step explanation:
Given that,
y=x+2 equation 1
2x-y=-4 equation 2
This is a simultaneous equation.
Substitute equation 1 into equation 2
2x-y=-4. Since y=x+2
2x-(x+2) = -4
2x-x-2 = -4
x-2 = -4
x = -4+2
x = -2
Also from equation 1
y=x+2
Since x=-2
y=-2+2
y=0
Then, solution (x, y) = (-2,0)
Answer: x = -2, y = 0
Step-by-step explanation:
[tex]y=x+2\\2x-y=-4[/tex]
Substitute y = x+2 in [tex]2x-y=-4[/tex]
Then we get, [tex]2x-(x+2)=-4[/tex]
[tex]2x-x-2=-4\\x-2=-4\\x=-4+2\\x=-2[/tex]
Then substitute x = -2 in any equations, just only one equation. For me, I'd substitute x = -2 in y = x+2
[tex]y=-2+2y=0[/tex]
So the answer is x = -2 and y = 0